К вопросу о синтезе карбазола из фенилгидразина и циклогексанона - Лопатинский В. П. Вадим Петрович; Ровкина Н. М. Нэля Михайловна; Батырова Л. М. Людмила Михайловна; Гарганеева Н. К. Наталья Константиновна; Горшкова Л. М. Людмила Михайловна; Козлов О. Д. Олег Дмитриевич (Томск, 1985)
Деп. в ОНИИТЭХим, г. Черкассы, 02.01.85, № 4-ХП-85.